Field epidemiology capacity of the national veterinary services of Lao PDR: An online survey - Subharat, Supatsak; Meunsene, Dethaloun; Putthana, Vannaphone; Tiwari, Harish; Firestone, Simon M. (Frontiers in Veterinary Science, 2023)
Capacity in veterinary epidemiology is critical to detect, respond to and control infectious diseases. Laos veterinary service is limited by having only a small number of veterinarians who graduated from overseas. Animal science graduates support the majority of the Laos veterinary services. The veterinary program was established in 2009 at the National University of Laos. We aimed to understand the national veterinary epidemiology capacity and identify gaps and training needs. A cross-sectional online study was conducted in 2021 targeting central (DLF), provincial (PAFO) and district (DAFO) government animal health officers and veterinary/animal science academics (n = 332). The questionnaire addressed skills, experiences and perceived training needs in outbreak investigation, disease surveillance, data management & analysis, epidemiological surveys, One Health, leadership & communication and biosecurity. A descriptive analysis was performed and associations between demographic factors and epidemiological skills were examined. In total, 205 respondents completed the questionnaire (61.8% response rate). Respondents reported low or no skills and experience in data management and analysis, epidemiological surveys and One Health. In contrast, higher but limited skills and experiences were reported in outbreak investigation, disease surveillance and biosecurity. Previous epidemiology training was primarily associated with stronger experiences in veterinary epidemiology competencies, followed by respondents that had completed a veterinary degree, highlighting the value of the currently available epidemiology training and veterinary-trained personnel in Lao PDR. This study could help inform the Laos government in its policy planning for field veterinary epidemiology capacity and future training.